2017
DOI: 10.1149/2.0151801jss
|View full text |Cite
|
Sign up to set email alerts
|

Review—Light Emission from Thin Film Solar Cell Materials: An Emerging Infrared and Visible Light Emitter

Abstract: In the last decade, there have been extensive studies on fabrication and physics of thin-film solar cell materials and devices. Many high-efficiency solar cell devices have been developed, and the knowledge gained in these studies can be used advantageously to produce bright light-emitting devices. In this review, we summarize recent luminescence spectroscopic studies on new solar-cell materials and discuss their photocarrier dynamics with respect to efficient light emission. © The Author(s) This special iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 124 publications
(190 reference statements)
0
10
0
Order By: Relevance
“…[9][10][11][12][13] PL spectroscopy can be used to understand the carrier dynamics of not only the materials themselves but also solar cell devices. [14][15][16] Optical studies have revealed that halide perovskites feature few localized levels within the bandgap and a corresponding sharp absorption edge, high PL efficiency, and excellent carrier properties, such as a long carrier lifetime, all of which together explain the high PCEs of perovskite solar cells. [17][18][19][20] Furthermore, it has been revealed that halide perovskites possess unique thermo-optic properties [21][22][23][24] and nonlinear optical responses, 25,26 which has attracted broad interest from researchers in fundamental semiconductor physics and device applications.…”
Section: Fundamental Semiconductor Properties Of Halide Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] PL spectroscopy can be used to understand the carrier dynamics of not only the materials themselves but also solar cell devices. [14][15][16] Optical studies have revealed that halide perovskites feature few localized levels within the bandgap and a corresponding sharp absorption edge, high PL efficiency, and excellent carrier properties, such as a long carrier lifetime, all of which together explain the high PCEs of perovskite solar cells. [17][18][19][20] Furthermore, it has been revealed that halide perovskites possess unique thermo-optic properties [21][22][23][24] and nonlinear optical responses, 25,26 which has attracted broad interest from researchers in fundamental semiconductor physics and device applications.…”
Section: Fundamental Semiconductor Properties Of Halide Perovskitesmentioning
confidence: 99%
“…89 This is why determinations of carrier lifetimes by using time-resolved PL measurements have been indispensable in the photovoltaic field. 14,15 The PL lifetime is typically measured with pulsed laser excitation, while an actual solar cell operates under the steady-state conditions of continuous solar illumination. The photogenerated carrier densities often differ very much between pulsed laser excitation and continuous light illumination.…”
Section: Excitation Fluence Dependence Of Pl Lifetimesmentioning
confidence: 99%
“…In our investigations into the photophysics of semiconductors, we have found that a semiconductor can be considered potentially useful for optoelectronic device applications if it exhibits strong PL that corresponds to the material-specific band-gap energy. [11,33] We have shown that it is even possible to characterize the electrical properties of optoelectronic devices such as solar cells by using band-edge PL. [33,34] Compared with electrical conduction, PL properties are much more sensitive to impurities and defects.…”
Section: Photoluminescence Spectramentioning
confidence: 99%
“…[11,33] We have shown that it is even possible to characterize the electrical properties of optoelectronic devices such as solar cells by using band-edge PL. [33,34] Compared with electrical conduction, PL properties are much more sensitive to impurities and defects. Thus, crystals with extremely high quality are needed for PL measurements to be able to detect intrinsic optical processes.…”
Section: Photoluminescence Spectramentioning
confidence: 99%
“…In the past few years, organic-inorganic hybrid perovskite solar cells (PSCs) have gained attention due to their high power conversion efficiency (PCE) and low cost [1][2][3][4][5][6][7][8][9]. In 2013, the first p-i-n-structure PSC was fabricated and it had a PCE of 3.9% [10].…”
Section: Introductionmentioning
confidence: 99%